Post-traumatic stress disorder and postpartum depression and their reported association with recent labor and delivery: a questionnaire survey cohort. (August 2020) - Freedman, S.A.; Reshef, S.; Weiniger, C.F.
Highlights: Postpartum women may suffer post-traumatic stress disorder (PTSD) and depression. Relationship between the traumatic event and delivery is insufficiently described. Worst trauma unrelated to or pre-dating delivery associated with higher PTSD scores. Many women with probable postpartum PTSD had clinical levels of fear of childbirth. Women should be assessed for PTSD during pregnancy to identify pre-existing symptoms. Abstract: Background: We aimed to investigate the index traumatic event associated with post-traumatic stress disorder (PTSD) and evaluate the timing of the onset of symptoms in relation to the recent delivery. Methods: Questionnaire study regarding prior exposure to traumatic events, PTSD, postpartum depression (PPD) and fear of childbirth among women two to 12 months postpartum, recruited via targeted internet sites. Results: Questionnaires were completed by 143 women, with PPD reported by 22 (15.4%), probable PTSD by 11 (7.7%), and fear of childbirth by 14 (9.8%). Overall, 97 (67.8%) women reported a prior traumatic event: 16 (16.5%) reported the recent delivery to be the worst traumatic event and that symptoms began subsequent to this delivery; 17 (17.5%) reported the worst traumatic event was not the recent delivery but symptoms had started postpartum. Significantly higher symptom levels suggestive of PTSD and PPD were found in women whose trauma event was not delivery, yet symptoms started postpartum. Women whose traumatic event pre-dated the delivery also showed significantly higher symptom levels of PTSD. More than half of those describing PTSD related to the recent delivery presented with clinically relevant levels of fear of childbirth, compared with less than a third of women whose PTSD was related to a different event. Conclusion: PTSD identified postpartum may not be linked to the recent delivery and often pre-dates it. Future studies should identify the trigger traumatic event responsible for PTSD symptoms, to enable a more accurate picture of the reasons for PTSD and fear of childbirth.